Strengthening of GFRP Reinforced Concrete Slabs with Openings - Mohammed Abas Golham; Ali Hussein Ali Al-Ahmed (Journal of Engineering, 2024)
Using fiber-reinforced polymer (FRP) could effectively improve the strength and endurance of reinforced concrete (RC) constructions. This study evaluated the flexural behavior of one-way concrete slabs with openings reinforced with glass fiber-reinforced polymers (GFRP) bars. It strengthened using carbon fiber-reinforced polymer (CFRP) sheets around the openings. The experimental program of this study is adopted by casting and testing four one-way concrete slabs with dimensions of (150*750*2650) mm. These slabs are divided into two groups based on whether they were strengthened or un-strengthened. For each group, two different openings (either one rectangular or two square) measured 250*500 mm and 250*250 mm, respectively, were fabricated within the pure flexural zone of the specimens. The experimental results indicate that using CFRP strips increases the maximum load capacity by around 29% for the slab with one rectangular opening and 21% for the slab with two square openings compared to the un-strengthened slabs. On the other hand, the deflection at a service load is decreased by about 35% and 37% for the slabs mentioned above, respectively.